Bacterial Outer Membrane Permeability Increase Underlies the Bactericidal Effect of Fatty Acids From Hermetia illucens (Black Soldier Fly) Larvae Fat Against Hypermucoviscous Isolates of Klebsiella pneumoniae - Mohamed, Heakal; Marusich, Elena; Afanasev, Yuriy; Leonov, Sergey (Frontiers in Microbiology, 2022)
Behind expensive treatments, K. pneumoniae infections account for its high mortality rates and extended hospitalization. We evaluated the antimicrobial activity of lipids isolated from Hermetia illucens (Hi) larvae fat against Klebsiella pneumoniae standard NDM-1 carbapenemase-producing ATCC BAA-2473 strain, along with wild-type hypermucoviscous clinical isolate, strain KPi1627, and environmental isolate, strain KPM9, that were resistant to multiple antibiotics (MDR) as demonstrated by susceptibility assay. For the first time, we demonstrated that the inhibition zone diameter (IZD) of fatty acid-containing extract (AWME3) of Hi larvae fat tested at 20 mg/mL was 16.52±0.74 mm, and 14.23±0.35 mm against colistin-resistant KPi1627and KPM9, respectively in disk diffusion assay. It was 19.72±0.51 mm against colistin-susceptible K. pneumoniae ATCC BAA-2473. The minimum inhibition concentration (MIC) and the minimum bactericidal concentration (MBC) were 250 µg/mL for all tested bacteria strains, indicating the bactericidal effect of AWME3. The half of the minimum inhibitory concentration (MIC50) values were 155.6±0.009 µg/mL, and 160.1±0.008 µg/mL against KPi1627 and KPM9 isolate, respectively, and 149.5±0.013 µg/mL, against ATCC BAA-2473 strain in the micro-dilution assay. In addition to the fact that the AWME3 dose-dependently increased the bacterial cell membrane permeability as determined by the relative electric conductivity (REC) of K.pneumoniae ATCC BAA-2473 suspension, none of the strains did build up resistance to extended AWME3 treatment. Free fatty acids (FFAs) and their derivatives were the significant substances among 33 compounds identified by GC-MS analysis of AWME3. Cis-oleic and palmitoleic acid represent the most abundant unsaturated FAs (UFA), while palmitic, lauric, stearic, and myristic acids were the most abundant saturated FAs (SFA) of the AWME3content. Our study provides a rationale and utility of Hi larvae fat to develop natural biocidal resistance-free formulations that might be promising therapeutic against Gram-negative MDR bacteria causing nosocomial infections.